2017
DOI: 10.1158/0008-5472.can-16-2571
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Prenatal and Early-Life Tobacco Smoke Exposure and Frequency of Common Gene Deletions in Childhood Acute Lymphoblastic Leukemia

Abstract: Tobacco smoke exposure has been associated with risk of childhood acute lymphoblastic leukemia (ALL). Understanding the relationship between tobacco exposures and specific mutations may yield etiologic insights. We carried out a case-only analysis to explore whether prenatal and early-life tobacco smoke exposure influences the formation of leukemogenic genomic deletions. Somatic copy-number of 8 genes frequently deleted in ALL (CDKN2A, ETV6, IKZF1, PAX5, RB1, BTG1, PAR1 region, and EBF1) was assessed in 559 pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
1
24
0
1
Order By: Relevance
“…Maternal smoking is one of the most commonly studied risk factors for childhood ALL to date and has also been investigated in a molecular ALL subtype analysis, apparently the first study of its kind, in relation to any exposure. In a case-only study, that assessed the association between tobacco exposure during the early-life period and deletions in 8 genes commonly lost somatically in childhood ALL (CDKN2A, ETV6, IKXF1, PAX5, RB1, BTG1, PAR1 region, and EBF1), a positive association was observed between maternal smoking and the total number of deletions observed in these genes in tumor samples from cases of childhood ALL (117). Interestingly, the authors observed that B-ALL and hyperdiploid ALL experienced fewer deletions of these genes while T-ALL and ETV6-RUNX1 B-ALL cases experienced one or more deletions in the genes under study.…”
Section: Risk Of All By Molecularly Defined Mutation Subtypementioning
confidence: 99%
“…Maternal smoking is one of the most commonly studied risk factors for childhood ALL to date and has also been investigated in a molecular ALL subtype analysis, apparently the first study of its kind, in relation to any exposure. In a case-only study, that assessed the association between tobacco exposure during the early-life period and deletions in 8 genes commonly lost somatically in childhood ALL (CDKN2A, ETV6, IKXF1, PAX5, RB1, BTG1, PAR1 region, and EBF1), a positive association was observed between maternal smoking and the total number of deletions observed in these genes in tumor samples from cases of childhood ALL (117). Interestingly, the authors observed that B-ALL and hyperdiploid ALL experienced fewer deletions of these genes while T-ALL and ETV6-RUNX1 B-ALL cases experienced one or more deletions in the genes under study.…”
Section: Risk Of All By Molecularly Defined Mutation Subtypementioning
confidence: 99%
“…Another limitation was the use of tumor‐only sequencing data to identify germline mutations. Although the extremely high sequencing depth enabled us to predict putative germline mutations with relatively high specificity (false positive rate ~10%), we may have missed germline mutations that resided in regions of somatic copy number loss; however, given the low frequency of somatic deletions in HD‐ALL, and that the 57 HD‐ALL patients were selected based on their lacking any of the eight most common gene deletions, this is unlikely to have significantly affected our findings. Our analyses were limited to known ALL‐related genes and recurrently mutated genes within the targeted sequencing results; thus, studies using whole exome or genome sequencing of large numbers of patients are required to obtain a more accurate frequency of predisposing mutations in HD‐ALL, especially given the range of different genes that likely contribute.…”
Section: Discussionmentioning
confidence: 97%
“…The proto-oncogene BMI1 is a member of the polycomb repressive complex 1, and is a negative regulator of the cellcycle checkpoint proteins p16 and p14ARF, 33 both of which are encoded by CDKN2A, the most frequently deleted gene in ALL tumors in both Latinos and non-Latino whites. 34 Hyperactivation of BMI1 promotes oncogenesis through increased cell proliferation and cell lifespan, 33 and BMI1 overexpression is commonly detected in childhood ALL, 35 in addition to several other hematological malignancies including AML 36 and B-cell non-Hodgkins lymphoma. 37 Overexpression of BMI1 is associated with poorer prognosis in childhood ALL 35 and in AML.…”
Section: Discussionmentioning
confidence: 99%